Pre-treatment of corn bran for production of arabinoxylan based prebiotics - Kaur,Manjyot (2020)
Arabinoxylan (AX) degrades to (arabino)xylooligosaccharides [(A)XOS] through enzymatic hydrolysis. AX and (A) XOS are considered as dietary fibers and are associated with many health benefits, including immunomodulatory activity. (A)XOS includes both xylooligosaccharides (XOS) and arabino xylooligosaccharides (AXOS). The current research aims to develop a process for production of xylan fibers, including data from the characterization of the raw material (corn bran) to the optimisation of the pretreatment process of CB by investigating the actions of sodium hydroxide (NaOH) and calcium hydroxide (Ca(OH)2) under oxidative conditions (using hydrogen peroxide) as pretreatment of corn bran in order to cause appreciable enzymatic digestibility. The best pre-treatment method was selected based on the yield, color, purity and texture of the xylan fibres, simplicity of the extraction process and scale-up possibilities. Pretreatment of CB with Ca(OH)2 and hydrogen peroxide (H2O2) overnight at 60°C gave an extraction yield of 25.64%. The arabinose/xylose (Ara/Xyl) ratio of the obtained xylan fibers was found to be 1.69 with an ash content of 6%. The purity of arabinoxylan obtained was only 4.36%. However, when double extraction was performed following the same process, the purity of obtained arabinoxylan increased to 34.47%. Single extraction with combined NaOH-Ca(OH)2 and H2O2 pretreatment overnight at 60°C gave an extraction yield of 55%. The arabinose/xylose (Ara/Xyl) ratio of the obtained xylan fibers was found to be 1.17 with an ash content of 21.2%. The purity of arabinoxylan obtained was 29.49%.
Keywords: pre-treatment; alkali; arabinoxylan; prebiotics; corn; probiotics; biotechnology; bioteknik